What is physiologging? Introduction to the theme issue, part 2 - Hawkes, L. A. (Philos Trans R Soc Lond B Biol Sci, 2021)
The physiological mechanisms by which animals regulate energy expenditure, respond to stimuli and stressors, and maintain homeostasis at the tissue, organ and whole organism levels can be described by ‘physiologging’—that is, the use of onboard miniature electronic devices to record physiological metrics of animals in captivity or free-living in the wild. Despite its origins in the 1960s, physiologging has evolved more slowly than its umbrella field of biologging. However, the recording of physiological metrics in free-living animals will be key to solving some of the greatest challenges in biodiversity conservation, issues pertaining to animal health and welfare, and for inspiring future therapeutic strategies for human health. Current physiologging technologies encompass the measurement of physiological variables such as heart rate, brain activity, body temperature, muscle stimulation and dynamic movement, yet future developments will allow for onboard logging of metrics relating to organelle, molecular and genetic function. This article is part of the theme issue ‘Measuring physiology in free-living animals (Part II)’.